Using the principle of mathematical induction, prove that \[\frac{d^{n}a}{dx^{n}}=\frac{(-1)^{n}n!}{(x+5)^{n+1}}\] for \(a=\frac{1}{x+5}\).

Just explain me the inductive step! Thanks :)

Using the principle of mathematical induction, prove that \[\frac{d^{n}a}{dx^{n}}=\frac{(-1)^{n}n!}{(x+5)^{n+1}}\] for \(a=\frac{1}{x+5}\).

Just explain me the inductive step! Thanks :)

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

There are no comments in this discussion.